AKADEMİSYENLERDE DUYGUSAL ZEKÂ FAKTÖRLERİNİN TÜKENMİŞLİK FAKTÖRLERİ İLE İLİŞKİSİNE YÖNELİK BİR ARAŞTIRMA: KOCAELİ ÜNİVERSİTESİ ÖRNEĞİ (A RESEARCH ABOUT THE RELATIONSHIP BETWEEN EMOTIONAL INTELLIGENCE FACTORS AND BURNOUT FACTORS OF ACADEMICIANS: CASE OF KOCAELİ UNIVERSITY) - Gönül KONAKAY (Dokuz Eylül Üniversitesi Sosyal Bilimler Enstitüsü Dergisi, 2013)
The aim of the study is to investigate if there is a relationship between levels of emotional intelligence and burnout among academicians. In this context, for the theoretical part, emotional intelligence and burnout was investigated by reviewing the literature and explaining the relationship between emotional intelligence and burnout was determined as the sub-aim of the study.Emotional intelligence of academicians will be determined as Positive Emotional Evaluation, Positive Emotional Management, and Empathetic Susceptibility dimensions by using Chan’s EI12 scale. It will be investigated if the emotional intelligence of the academicians differs according to the demographic characteristics such as their term of employment, age, gender, title, field of education. Maslach Burnout Scale was used to evaluate the burnout dimension. In this study, the burnout dimensions were determined as Emotional Exhaustion, Personal Achievement, Emotional Toughness, Emotional Softening and Depersonalization. The changes in emotional intelligence and elements of burnout were investigated using the demographic variables. During the research conducted to determine the relationship between emotional intelligence and burnout, t-test, variance analysis, factor analysis, correlation and regression analyses were used to test the hypotheses. The relationship was found between emotional intelligence and burnout.